Case Report: a rare primary gastric choriocarcinoma revealed on 18F-FDG PET/CT - Zhao, Yi; Diao, Wei; Li, Suping; Yang, Mengxi; Cheng, Zhuzhong (Frontiers in Oncology, 2023)
Choriocarcinoma is an exceptionally aggressive trophoblastic cell tumor that that typically originates in gonadal tissues, with rare occurrences outside the gonads, including the mediastinum, retroperitoneum, and intracranial sites. However, it rarely occurs in the stomach. Herein, we presented a case of primary gastric choriocarcinoma in a 27-year-old female patient who found multiple liver masses detected during physical examination, accompanied by remarkably elevated human chorionic gonadotropin levels. The 18 F-FDG PET/CT scan suggested ring-shaped intense uptake masses located in the gastric sinus and liver, and no significance in the pelvic region. Final histopathology indicated primary choriocarcinoma of the stomach. This case illustrates that 18 F-FDG PET/CT is an essential imaging technique for the clinical diagnosis and stage of primary choriocarcinoma.